Apolipoprotein E loss of function: Influence on murine brain markers of physiology and pathology - Heather Buchanan; Claire Hull; Maria Cacho Barraza; Mirela Delibegovic; Bettina Platt (Aging Brain, 2022)
The canonical role of Apolipoprotein E (ApoE) is related to lipid and cholesterol metabolism, however, additional functions of this protein have not been fully described. Given the association of ApoE with diseases such as Alzheimer’s Disease (AD), it is clear that further characterisation of its roles, especially within the brain, is needed.Therefore, using protein and gene expression analyses of neonatal and 6-month old brain tissues from an ApoE knockout mouse model, we examined ApoE’s contribution to several CNS pathways, with an emphasis on those linked to AD. Early neonatal changes associated with ApoE−/− were observed, with decreased soluble phosphorylated tau (p-tau, –40 %), increased synaptophysin (+36 %) and microglial Iba1 protein levels (+25 %) vs controls. Progression of the phenotype was evident upon analysis of 6-month-old tissue, where decreased p-tau was also confirmed in the insoluble fraction, alongside reduced synaptic and increased amyloid precursor protein (APP) protein levels. An age comparison further underlined deviations from WT animals and thus the impact of ApoE loss on neuronal maturation.Taken together, our data implicate ApoE modulation of multiple CNS roles. Loss of function is associated with alterations from birth, and include synaptic deficits, neuroinflammation, and changes to key AD pathologies, amyloid-β and tau.